The Influence Of Product Quality And Promotion On Customer Satisfaction Keisha Collection Pangkalan Balai Clothing Store - Yolanda Veybitha; Ima Andriyani; Muhni Pamuji; Andini (CV Putra Publisher, 2024)
The purpose of this research is to determine the effect of product quality and promotion on customer satisfaction at the Keisha Collection Pangkalan Balai clothing store. The variables used in this research are Product Quality (X1), Promotion (X2), Customer Satisfaction (Y). The population of this research is the customers of the Keisha Collection Pangkalan Balai clothing store, totaling 330 people. The sample for this research was 77 people. The type of research used is quantitative, the analysis technique used is multiple linear regression, hypothesis testing using the F test and t test. The regression results obtained the equation Y= 1.335 + 0.412 X1 + 0.243 X2. Which means that customer satisfaction is influenced by product quality and promotion. The results of the F test obtained Fcount (86,000), meaning that there is a simultaneous influence of Product Quality and Promotion on Customer Satisfaction. The results of the t test for the Product Quality variable obtained tcount (4.717), and the Promotion variable obtained tcount (2.685), meaning that Product Quality and Promotion partially influence Customer Satisfaction at the Keisha Collection Pangkalan Balai Clothing Store.